2017
DOI: 10.1080/14737167.2017.1366857
|View full text |Cite
|
Sign up to set email alerts
|

Indirect costs of diabetes and its impact on the public finance: the case of Poland

Abstract: Estimated indirect cost of diabetes can be a useful input for health technology analyses of drugs or economic impact assessments of public health programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…For instance, a study conducted by the American Diabetes Association (ADA) using data sources from national surveys, Medicare and claims databases for the commercially insured population in the USA found that disease-related disability was the biggest component (42%) of indirect cost 20. Another study in Poland using the national administrative database and human-capital approach found that presenteeism was dominant at 75% of the indirect costs 21. In terms of costs as a percentage of GDP, direct non-medical and indirect cost accounted for 6.3% of Thailand per capita GDP in 20083 and 7.7% of Brazil per capita GDP in 2012 22.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study conducted by the American Diabetes Association (ADA) using data sources from national surveys, Medicare and claims databases for the commercially insured population in the USA found that disease-related disability was the biggest component (42%) of indirect cost 20. Another study in Poland using the national administrative database and human-capital approach found that presenteeism was dominant at 75% of the indirect costs 21. In terms of costs as a percentage of GDP, direct non-medical and indirect cost accounted for 6.3% of Thailand per capita GDP in 20083 and 7.7% of Brazil per capita GDP in 2012 22.…”
Section: Discussionmentioning
confidence: 99%
“…A study on disease burdens showed that in Poland, the direct costs of diabetes treatment doubled in the 2005–2009 period [ 2 ]. It is estimated that during the years 2012–2014 in Poland, diabetes and its complications were responsible for over 82,000 lost working years, which resulted in over USD 1.9 billion of total indirect costs [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results show that HF in Poland accounted for indirect costs of €871.9 million in 2012 and grew to €945.3 million in 2015, generating an 8.4% increase. The productivity losses due to HF were 25% higher than those associated with breast cancer in Poland [ 18 ] but lower than in the case of diabetes (2 billion US$) [ 23 ] (2014 estimates for all three diseases). The production lost due to HF was an equivalent of 0.212–0.224% of GDP, and no clear time trend was observed; the costs declined in 2012 and 2013 and then increased in 2014.…”
Section: Discussionmentioning
confidence: 99%